Effect of Chicken Plasma Protein Powder on Performance and Cellular Immunity of Piglets - Yao, Wei; Zhi-Sheng, Wang; An-Guo, Zhou (Pakistan Journal of Nutrition, 2009)
The experiment was used to investigate the effect of Chicken’s plasma protein powder on performance and immunity in 32 crossbred piglets weaned at 28 day of age (4 groups of 4 each, 8.78±0.07 kg live weight). During 0-14 d, pigs were offered for different diets in both treatments, while received the same diet during the rest time of experiment. The effects of chicken’s plasma protein powder on performance, cellular immunity of weaned piglets were evaluated. The results indicated that during 0-14d, compared with the control group, Average Daily Gain (ADG), Average Daily Feed Intake (ADFI) of pigs fed with Chicken’s plasma protein increased by 65.50%, 37.11%, respectively (p